Administrative justice in India - Nayak, Radhakant (New Delhi, 1989)
Justice is a multi-dimensional and many splendoured dome. The literature on the subject is also immense. It covers extensive disciplines such as law, ethics, philosophy and theology. The meanings, content and components of justice are innumerable and diverse. Justice covers political, economic, social, legal and even distributive aspects. One hears of poetic justice and approba tive justice. Justice can be expressed in terms of absolute and relative, prescriptive and corrective, social and obligatory, and natural and moral. Some persons base it on the notions of right and wrong and others find it to be historical or scriptural. Still others describe justice as human and dialectical. Thus there can be as many meanings and definitions of justice as there are writers and thinkers. Hence, instead of entering into a controversy over the meaning and nature of justice, we tend to agree with Karl Popper who settles the controversy by saying, to ask for the meaning of justice is to raise 'an unimportant verbal question to which no definite answer can be given'. "But we have selected an important rather the most important-segment of justice for our study. Our effort is to study justice from the points of view of its structure and functions, in terms of the organisation or authority which handles it, the process adopted and the jurisdiction exercised for its dispensation. In other words, our focus is on that aspect of applied justice which constitutes the kernel of the modern admin istrative state.
Keywords: Administrative courts-India